Model Pembelajaran Jigsaw dan Problem based learning Berbasis Culturally Responsive Teaching (CRT) dalam Meningkatkan Hasil Belajar Sepak Bola Kelas X SMA Negeri 2 Semarang - Prastiyo, Fendy Eko; Zhannisa, Utvi Hinda; Waskitho, Tutur Lukas (Universitas PGRI Semarang, 2025)
The purpose of this study is to test the jigsaw learning model and problem-based learning based on culturally responsive teaching (CRT) in improving football learning outcomes of grade X students of SMA Negeri 2 Semarang The sampling technique applied is purposive sampling. This study uses a test as an instrument, the test used is a shooting test. The normality test, homogeneity test, and difference hypothesis test and t test are the analyses used in this study. Information was obtained that the average score of the students in the jigsaw learning approach group was 74.4 and the posttest results after treatment with jigsaw learning were on average 85. Meanwhile, the data of the problem based learning group before the treatment was carried out, the average student score was 75.3 and after the treatment, the student score changed, namely with a mean value or an average score of 85.06. It was interpreted that the hypothesis was rejected because there was no significant difference in the results of the students' pretest between the two treatment groups. The jigsaw learning model group provided an increase of 14.2%, while the problem-based learning model group provided an increase of 12.9%. The conclusion is that the use of jigsaw learning models and problem-based learning has a significant influence on football learning outcomes in grade X students of SMA Negeri 2 Semarang. The jigsaw learning model group is an effective learning model compared to the Problem based learning model on football learning outcomes in grade X students of SMA Negeri 2 Semarang.